ПРАВОВАЯ ИДЕЯ МЕСТНОГО САМОУПРАВЛЕНИЯ В СОВРЕМЕННОМ ОБЩЕСТВЕ. - Белиспаев., А. М. (Journal of actual problems of jurisprudence, 2016)
In the research paper “Legislative concept of local self-government in modern community” general theoretical-judiciary origins of a local selfgovernment are discussed. Development of autonomy is defined by the author as a perspective step towards institutional improvements of direct democracy in the Republic of Kazakhstan. With this intent the paper conducts legislative assessment of the current legislation and constitutional propositions.